Interlinkages between Urbanization and Climate Change: Identifying and Understanding the Challenges and the Prospects - Abhinav Alakshendra; Arjun Kumar; Simi Mehta (The Institute for Research and Community Services, Institut Teknologi Bandung, 2020)
India is urbanizing at an alarming rate and the impact of climate change is becoming more visible each passing day. The rapid urbanization and climate change have severe direct and indirect consequences, such as increasing poverty, inequality, massive displacement, public health concerns, and challenges of urban governance, among others. This paper identifies some of the most pressing issues faced by urban India in the context of climate change. It also details the interventions undertaken at the local, national, and international levels to counter the effect of the climate change. In addition, it critically evaluates the role of government organizations, especially in terms of undertaking regulatory and planning functions. The paper argues that the implementation of institutional reforms would enable the government to reach out to the private sector to improve urban service delivery. It also provides examples of best practices from India and the world in combating climate change through adaptation and mitigation approaches.Abstrak. India mengalami urbanisasi pada tingkat yang mengkhawatirkan dan dampak perubahan iklim menjadi terlihat setiap hari. Urbanisasi yang cepat dan perubahan iklim memiliki konsekuensi langsung dan tidak langsung yang parah, seperti antara lain meningkatnya kemiskinan, ketimpangan, pengungsian besar-besaran, masalah kesehatan masyarakat, dan tantangan tata kelola kota. Makalah ini mengidentifikasi beberapa masalah paling mendesak yang dihadapi oleh perkotaan India dalam konteks perubahan iklim. Makalah ini juga merinci intervensi yang dilakukan di tingkat lokal, nasional, dan internasional untuk melawan dampak perubahan iklim. Selain itu, secara kritis makalah ini mengevaluasi peran organisasi pemerintah, terutama dalam menjalankan fungsi pengaturan dan perencanaan. Makalah ini berpendapat bahwa pelaksanaan reformasi kelembagaan akan memungkinkan pemerintah menjangkau sektor swasta untuk membantu meningkatkan pelayanan perkotaan. Makalah ini juga memberikan contoh praktik terbaik dari India dan dunia dalam memerangi perubahan iklim melalui pendekatan adaptasi dan mitigasi.Kata kunci. Urbanisasi, perubahan iklim, keterkaitan, tata kelola kota, mitigasi.